PIECZA NAD LUDŹMI STARYMI W POLSKIM PRAWIE CYWILNYM I OPIEKUŃCZYM NA TLE PORÓWNAWCZYM - Kociucki, Leszek (Wydział Prawa i Administracji UAM, 1999)
The norms of law regulating the participation of the elderly in the conduct of civil law transactions (for example - disposing of a bank account, dealing with social insurance matters) as well in Poland as in many other countries have not been revised since many years and even, to a certain degree, have been neglected by the science and jurisprudence, despite of the fact of immense impact of these questions on the quality itself of the living conditions of the elderly. The norms in question are characterised with a lack of elasticity; or they do treat the elderly in the same way as fully valid participants in the conduct of civil law transactions (with the same duties and without any adequate protection because of the ageing) or the norms give some legal protection to the elderly however at the cost of their legal incapacitation. One of the main aims of the reform of the care of mature persons which was introduced in Austria, Sweden and Germany was a creation of legal framework for assistance to the elderly with no intervention in their private sphere. The article gives an attempt to determine the position of the care of the elderly within Polish law system, it presents also the present legal state and propositions of changing certain legislative dispositions. Synthetic and sometimes quite general formulation of Polish provisions made it possible for the courts to get an interpretation which diminishes possible intervention in the rights of persons under care. However, in many cases the help offered for the elderly occurs to be insufficient, so a change of respective law provisions is already desirable. Renouncing of the institution of legal incapacitation in its present form shall not only deprive the care of its undesirable effects but, in the same time, shall make it possible to assist the elderly in a way better adapted to concrete needs.
CARE OF THE ELDERLY IN POLISH CIVIL LAW AND GUARDIANSHIP PROVISIONS AGAINST COMPARATIVE BACKGROUND